PENGARUH PRODUCT DIFFERENTIATION TERHADAP KEPUTUSAN PEMBELIAN PIRANTI LUNAK JASA PENDIDIKAN PT. X - Tun Ganyang, Machmed (Economic Faculty, Attahiriyah Islamic University, 2018)
Nowadays the development of technology and the internet is progressing; with most people in Indonesia are already having smart phones and using the internet in their daily needs. No wonder the number of business opportunities that can be utilized, with the condition of almost all people are literate technologically, especially in big cities. This phenomenon promotes software education to be one of the business trends, and although it is a relatively new business, it is growing, in this case the business associated with PT. X which is one of the education software application companies that focuses on the field of education for the students from elementary schools to high schools/vocational schools. In this study, the researcher focus on the effects of product differentiation features in attracting students to buy the PT. X software applications. The result shows that the variable of Product Differentiation (X) has significant effect to purchase decision (Y). Keywords: product differentiation, purchase decision, e-learning, software applications